Control presupuestario y su influencia en las obras civiles de la Cia. Obrecit del cantón Mocache - Da Cruz Briones, Nelio Andres (2021)
The objective of this case study is on budgetary control, it is a mechanism that aims to calculate a series of deviations or variations, analyze or establish corrective actions. The company OBRECIT SA is carrying out an inefficient budget control and this presented several problems that significantly influence the achievement of the objectives and goals that are proposed in the contract, leading to a delay in the scheduling of the works due to lack of plans by part contracting entity, in its programming due to miscalculation of measurement, location of land and change of the budget item due to unexpected situations.